Analytical and numerical modeling of the transient behavior of an earth connection during the injection of an electromagnetic wave - Mohammed Chebout; Azizi Hakim; Daoud Sekki; Mohammed Charif Kihal; Marouane Kihal (ITEGAM-JETIA)
This paper is devoted to the study and modeling of the behavior of a grounding system. The latter is used for the protection of electrical installations and equipment against surges and various disturbances affecting these systems. The methods used for modeling are multiple for this, an analysis and a synthesis of these methods has been made. In this work, the Agrawal model was used, which is based on the line theory. The finite integration technique was used under the CST Software for the purpose of verifying the first results. At the end, the different factors that influence the response of grounding systems were studied to evaluate the impulse performance. First, we start by determining the current distribution along the excited electrode in order to characterize the grounding radiation over time. The last part of this work is based on a parametric study that takes into account the electrode burial depth as well as the resistivity jump between the electrode and the surface. The results obtained by our analytical model are compared and validated by the CST/EMC software. Good agreements are found between these approaches.